Theorizing and theory building in the safety sciences: A reflective inquiry. (August 2019) - Klockner, K.; Pillay, M.
Highlights: An examination of theory advancement for the safety sciences is reviewed. Developing theory can be understood for early career researchers or early career academics. Types of rationale on how to develop theory in the safety sciences is discussed. Abstract: Early career academics seeking to build and advance in their disciplines become recognised by their broad publishing of research papers. Most academic journals have a requirement that papers worthy of publication must contribute to and drive theory in the respective discipline. Whilst this publication requirement is understood by seasoned academics, it is not clear how early career researchers and/or early career academics learn how to go about building theory and how they can become an experienced theorist. Whilst many universities now offer an Early Career Research (ECR) program it may not deliver the required knowledge in how to go about theory building which seems to be akin to a tactic knowledge which more experienced and senior academics appear to have learnt only after many years in the professoriate. This paper was therefore interested in examining knowledge in the area of theory building, particularly as it pertains to the discipline of the safety sciences. The aim was to ascertain if there is was a methodology or key understanding that could be employed which would assist early career researchers and early career academics to understand how they can become theorists and therefore assist in their understanding of what theory building is in academic publication endeavours.